2017
DOI: 10.1038/npp.2017.289
|View full text |Cite
|
Sign up to set email alerts
|

Error-related Brain Activity as a Treatment Moderator and Index of Symptom Change during Cognitive-Behavioral Therapy or Selective Serotonin Reuptake Inhibitors

Abstract: Increased neural error monitoring, as measured by the error-related negativity (ERN), is a transdiagnostic neurobiological marker of anxiety. To date, little is known about whether the ERN can inform the choice between first-line anxiety disorder treatments and whether the ERN changes following treatment completion. The aim of the study was to therefore assess whether the ERN is a treatment moderator and index of symptom change during cognitive-behavioral therapy (CBT) or selective serotonin reuptake inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 59 publications
3
23
0
Order By: Relevance
“…On the other hand, these findings are consistent with evidence suggesting that the ERN is a trait-like marker of anxiety, based on evidence that the ERN does not change after successful treatment for instance, in OCD (Hajcak et al, 2008; Riesel, Endrass, Auerbach, & Kathmann, 2015), nor does it correlated with the degree of anxiety symptom change (e.g. (Kujawa, Weinberg, et al, 2016), but see (Gorka et al, 2018)), and can be present in unaffected first-degree relatives of patients with anxiety (Carrasco, Harbin, et al, 2013; Riesel, Endrass, Kaufmann, & Kathmann, 2011). Therefore, put together, future studies should utilize a depression comparison group to determine if this effect is specific to the co-occurrence of depression and anxiety or also seen in the absence of anxiety.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, these findings are consistent with evidence suggesting that the ERN is a trait-like marker of anxiety, based on evidence that the ERN does not change after successful treatment for instance, in OCD (Hajcak et al, 2008; Riesel, Endrass, Auerbach, & Kathmann, 2015), nor does it correlated with the degree of anxiety symptom change (e.g. (Kujawa, Weinberg, et al, 2016), but see (Gorka et al, 2018)), and can be present in unaffected first-degree relatives of patients with anxiety (Carrasco, Harbin, et al, 2013; Riesel, Endrass, Kaufmann, & Kathmann, 2011). Therefore, put together, future studies should utilize a depression comparison group to determine if this effect is specific to the co-occurrence of depression and anxiety or also seen in the absence of anxiety.…”
Section: Discussionsupporting
confidence: 87%
“…However, despite this recent study, the evidence of further significant changes of abnormal electrophysiological responses is still insufficient, particularly regarding the early processing of internal and external stimuli. For example, in performance monitoring, no study has yet found any evidence of significant changes of the enhanced ERPs evoked by the analysis of internal signals in patients suffering from an internalizing psychological disorder [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…According to the reinforcement-learning theory, the Ne/ERN reflects a dopaminergic signal, sent from subcortical to cortical brain regions, which calls for adjustments of inaccurate performances [19]. Starting from the evidence of abnormal processing of errors in internalizing psychopathologies, some recent studies have investigated whether short periods of treatment induce a normalization of the augmented amplitude of the Ne/ERN in patients [7][8][9][10][11]. Despite substantial reductions of the symptoms after psychotherapy, these studies reported no significant effect of treatment on the Ne/ERN amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…Both biomarker and mechanism differ from an endophenotype, which describes an intermediate expression of genetic risk, usually in psychiatric populations (Iacono, ; Insel & Cuthbert, ). Fortuitously, frontal midline theta and related ERP features appear to be viable neural mechanisms (Section 3.1), endophenotypes (Kang et al, ; Zlojutro et al, ), diagnostic tools (Figure c), and predictors of treatment response (Burkhouse et al, ; Gorka et al, ) for patient groups defined by frontal dysfunction. These signatures can be up‐ and downregulated with pharmacology (Jocham & Ullsperger, ) and transcranical electric current (Reinhart & Woodman, ; Reinhart, Zhu, Park, & Woodman, ), demonstrating causal control over this signal and downstream effects on network instantiation and behavior in humans.…”
Section: Clinical Practicementioning
confidence: 99%
“…Video recording is commonly embedded with the signal (white sphere with black circle at top). These features demonstrate that the infrastructure already exists to capitalize upon any novel taskbased assessment of an EEG feature that contributes to diagnosis or prognosis for neurological or psychiatric disease [Colour figure can be viewed at wileyonlinelibrary.com] | 9 of 13 CAVANAGH 2016; Gorka et al, 2018) for patient groups defined by frontal dysfunction. These signatures can be up-and downregulated with pharmacology (Jocham & Ullsperger, 2009) and transcranical electric current (Reinhart & Woodman, 2014;Reinhart, Zhu, Park, & Woodman, 2015), demonstrating causal control over this signal and downstream effects on network instantiation and behavior in humans.…”
Section: Mechanisms To Biomarkersmentioning
confidence: 99%